A Study of Maintenance-Related Education in Swedish Engineering Programs - Mirka Kans (Education Sciences, 2021)
Engineers of today require a holistic understanding of the lifecycle of products and processes, from conceptualization to operations. Maintenance and reliability are areas receiving increased attention due to the contribution to sustainable industry practices. The related literature describes ways to strengthen the education with respect to curricula and teaching, but studies on the extent and content of maintenance-related education in engineering programs are lacking. The purpose of this study is to describe the maintenance-related education content in Swedish engineering programs. The main objects of study are the curricula and courses of engineering programs in Sweden. In total, 123 Bachelor of Engineering and 119 Master of Engineering programs were studied, as well as 36 maintenance-related courses. It was found that 12% of the engineering programs include one or more maintenance-related course, either mandatory or elective. On the Master of Engineering level, only 4% of the programs include mandatory maintenance-related courses. The corresponding number for Bachelor of Engineering programs is 15%. The courses are typically of 6–7.5 credits, but as low as under one credit worth of maintenance-related content is seen, as well as two specialized programs offering up to 60 credits. Of the 36 courses, 20 have a distinct maintenance focus, 2 are degree thesis courses, and 2 are within reliability engineering, while the rest have a focus in other areas. The lack of maintenance-related education makes future engineers less prepared to make good decisions and judgments that might affect the operational phase of the product or system.